Eye Movement Recordings: Practical Applications in Neurology - Rizzo, John-Ross; Beheshti, Mahya; Dai, Weiwei; Rucker, Janet C. (Seminars in Neurology, 2019)
Accurate detection and interpretation of eye movement abnormalities often guides differential diagnosis, discussions on prognosis and disease mechanisms, and directed treatment of disabling visual symptoms and signs. A comprehensive clinical eye movement examination is high yield from a diagnostic standpoint; however, skillful recording and quantification of eye movements can increase detection of subclinical deficits, confirm clinical suspicions, guide therapeutics, and generate expansive research opportunities. This review encompasses an overview of the clinical eye movement examination, provides examples of practical diagnostic contributions from quantitative recordings of eye movements, and comments on recording equipment and related challenges.
Keywords: saccades; ocular flutter; nystagmus; video-oculography; eye movements